2020
DOI: 10.1109/access.2020.2977817
|View full text |Cite
|
Sign up to set email alerts
|

Securing Smart City Surveillance: A Lightweight Authentication Mechanism for Unmanned Vehicles

Abstract: The significance of the Internet of Drones (IoD) is increasing steadily and now IoD is being practiced in many military and civilian-based applications. IoD facilitates real-time data access to the users especially the surveillance data in smart cities using the current cellular networks. However, due to the openness of communication channel and battery operations, the drones and the sensitive data collected through drones are subject to many security threats. To cope the security challenges, recently, Sriniva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
142
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(143 citation statements)
references
References 41 publications
0
142
0
1
Order By: Relevance
“…In the surveyed papers, the security issues were considered in [7,20,30,31], while in others they were not focused. Comparing to the analyzed papers, we aim to offer a secure remote health monitoring model in cloud-based IoT environment using data mining methods for early disease diagnosis which uses a lightweight block encryption method that is a proper solution for constrained medical IoT resources [42] which has not been focused in the studied papers. Therefore, the main contribution or advantage of our proposed model comparing to the previous papers is considering confidentiality and security issues in an operative manner regarding the limitations in IoT resources.…”
Section: Security Solutions In Iot Medical Data Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the surveyed papers, the security issues were considered in [7,20,30,31], while in others they were not focused. Comparing to the analyzed papers, we aim to offer a secure remote health monitoring model in cloud-based IoT environment using data mining methods for early disease diagnosis which uses a lightweight block encryption method that is a proper solution for constrained medical IoT resources [42] which has not been focused in the studied papers. Therefore, the main contribution or advantage of our proposed model comparing to the previous papers is considering confidentiality and security issues in an operative manner regarding the limitations in IoT resources.…”
Section: Security Solutions In Iot Medical Data Managementmentioning
confidence: 99%
“…Generally, encryption plays a curtail role in making IoT systems secure. As an effective technique in block encryption methods, Substitution Box (S-Box) has an important impact [42,43,45,46]. Due to the constrained resources of IoT devices, providing lightweight S-Boxes is a challenge.…”
Section: Data Security Providingmentioning
confidence: 99%
“…Srinivas et al [7] an AKE scheme for IoD, which is insecure against impersonation and privilege insider attacks. Srinivas et al's scheme also does not scale well as demonstrated in [13]. Z.Lv et al [6] presented a security solution based on convolution neural networks for the IoD environment.…”
Section: Related Workmentioning
confidence: 99%
“…Let U A be a legit user of the system and knows the identity of another legal user U i . Following procedure can be adopted by U A to impersonate as a U i : 1) The U A fetches W j corresponding to SID j from RC's verifier table [51], picks an arbitrary nonce R A rand1 and calculates:…”
Section: User Impersonation Attackmentioning
confidence: 99%